Конформацiйнi ефекти i спектри фотолюмiнесценцiї нанокомпозитiв рiдкий кристал 5CB–вуглецевi нанотрубки - Klishevich, G. V.; Curmei, N. D.; Lebovka, N. I.; Melnyk, V. I. (Publishing house "Academperiodika", 2019)
Specific temperature dependences (10–300 K) of the emission band maximum, its intensity and half-width in the luminescence spectra of 5CB liquid crystals and 5CB+carbon nanotube nanocomposites are observed. The analysis of the luminescence spectra and thermal properties of the studied systems has shown that the observed features are due to polymorphic transformation of 5CB and conformational changes of its molecules.